Floods, landscape modifications and population dynamics in anthropogenic coastal lowlands: The Polesine (northern Italy) case study - Viero, Daniele P.; Roder, Giulia; Matticchio, Bruno; Defina, Andrea; Tarolli, Paolo (The Science of the total environment, 2019)
It is widely recognized that the complex relationship between humans, soil, and water has become increasingly complicated due to anthropogenic activities, and is further expected to worsen in the future as a result of population dynamics and climate change. The present study aims at shedding light on the multifaceted links between floods, landscape modifications, and population dynamics in anthropogenic coastal lowlands, using a large flood-prone area (the Polesine Region, northeastern Italy) as a significant case study. Based on the analysis of historical events and the results of hydraulic modeling, it is shown that human interventions on both the landscape and the subsoil have substantially altered the flood dynamics, exacerbating hydraulic hazard. Furthermore, the combined analysis of people and assets exposure to inundation reveals that flood risk is not properly taken into account in land-use planning, nor it is properly understood by people living in areas subject to low-probability, high-impact flood events. [Display omitted] •Lowlands are dynamic systems shaped by a wealth of anthropogenic activities.•Important landscape modifications and land subsidence occurred in the last 60 years.•Effects on flooding dynamics and on flood hazard were assessed with a modeling study.•Population spatial distribution changed not in view of reducing exposure to floods•Land use management and urbanization should account for flood risk properly.